Certifying Optimality in Hybrid Control Systems via Lyapunov-like Conditions. Issue 16 (2019) - Ferrante, Francesco; Sanfelice, Ricardo G.
Abstract: We formulate an optimal control problem for hybrid systems with inputs and propose conditions for the design of state-feedback laws solving the optimal control problem. The optimal control problem has the flavor of an infinite horizon problem, but it also allows solutions to have a bounded domain of definition, which is possible in hybrid systems with deadlocks. Design conditions for optimal feedback laws are obtained by relating a quite general hybrid cost functional to a Lyapunov like function. These conditions guarantee closed-loop optimality and are given by constrained steady-state-like Hamilton-Jacobi-Bellman-type equations. Applications and examples of the proposed results are presented.